2010
DOI: 10.1210/en.2010-0799
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Effects of Brain-Derived Neurotrophic Factor Blockade in an Androgen-Sensitive Neuromuscular System

Abstract: In adult male rats, androgens are necessary for the maintenance of the motoneurons and their target muscles of the sexually dimorphic, steroid-sensitive spinal nucleus of the bulbocavernosus (SNB) neuromuscular system, regulating motoneuron and muscle morphology, function, and expression of trophic factors. Castration of males results in somal, dendritic, and muscle atrophy as well as increases in brain-derived neurotrophic factor (BDNF) in the target musculature. Because BDNF can have either facilitative or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…Interestingly, castration markedly elevated BDNF protein in the SNB target musculature and treatment with trkB IgG prevented the typical castration-induced dendritic atrophy; dendrite lengths in these animals were similar to those of gonadally intact males treated with trkB IgG. This was the first demonstration that the dendritic arbors of the highly androgen-sensitive SNB motoneurons could be maintained in the absence of androgens, and further suggested that the elevated BDNF levels in muscle were responsible for regressive changes in SNB morphology (Verhovshek and Sengelaub, 2010b). Together, these results suggest that BDNF exerts regulatory effects on SNB dendrites, because when the actions of BDNF are blocked, dendritic hypertrophy occurs, and castration-induced somal atrophy is prevented.…”
Section: Bdnf-androgen Interactions: Maintenance Of Structurementioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, castration markedly elevated BDNF protein in the SNB target musculature and treatment with trkB IgG prevented the typical castration-induced dendritic atrophy; dendrite lengths in these animals were similar to those of gonadally intact males treated with trkB IgG. This was the first demonstration that the dendritic arbors of the highly androgen-sensitive SNB motoneurons could be maintained in the absence of androgens, and further suggested that the elevated BDNF levels in muscle were responsible for regressive changes in SNB morphology (Verhovshek and Sengelaub, 2010b). Together, these results suggest that BDNF exerts regulatory effects on SNB dendrites, because when the actions of BDNF are blocked, dendritic hypertrophy occurs, and castration-induced somal atrophy is prevented.…”
Section: Bdnf-androgen Interactions: Maintenance Of Structurementioning
confidence: 79%
“…Blockade of BDNF signaling using trkB IgG resulted in hypertrophy of the SNB target musculature in gonadally intact male rats, and muscle weights were significantly greater for trkB IgG-treated animals compared to controls (Verhovshek and Sengelaub, 2010b). Similarly, trkB IgG treatment in castrated males attenuated the castration-induced decrease in SNB target muscle weight (Verhovshek and Sengelaub, 2010b).…”
Section: Bdnf-androgen Interactions: Maintenance Of Structurementioning
confidence: 96%
See 1 more Smart Citation
“…It was suggested that testosterone exerts its protective effects by maintaining BDNF levels in dendrites, because testosterone treatment after gonadectomy restored BDNF levels in the motorneuron dendrites and prevented dendritic atrophy (Ottem et al 2007). On the other hand, trkB-IgG, a scavenger of BDNF, led to protection from the deleterious effects of castration on motorneurons; the authors suggested that testosterone normally suppresses BDNF levels (Verhovshek et al, 2010). …”
Section: Bdnf and The Mossy Fibers In Male Ratsmentioning
confidence: 99%
“…This work shows that activation of AR within the LA muscles itself changes the morphology of the innervating motoneuron cell bodies within the SBN (Rand and Breedlove, 1995). This is thought to occur in part as a result of AR-dependent expression of brain-derived neurotrophic factor (BDNF) in the muscle cells, which is retrogradely transported from the muscle to the motoneuron soma (Verhovshek et al, 2010; Verhovshek et al, 2013) where it then acts via its receptor, tyrosine-related kinase B (trkB), to enhance motoneuron size and dendritic arbor (Verhovshek and Sengelaub, 2010). IGF-I produced locally in muscle tissue is also retrogradely transported to the spinal cord to induce neurotrophic effects (Kaspar et al, 2003; Dobrowolny et al, 2005).…”
Section: Anatomy and Physiology Of Courtshipmentioning
confidence: 99%